1992
DOI: 10.1042/cs0820543
|View full text |Cite
|
Sign up to set email alerts
|

Lithium pretreatment affects renal and systemic responses to angiotensin II infusion in normal man

Abstract: 1. Renal and systemic responses to infusion of angiotensin II (1.25 and 2.5 ng min-1 kg-1 body weight) were examined in ten normal males 12 h after single doses of 750 mg of lithium carbonate, 250 mg of lithium carbonate (n = 6) or placebo. 2. Baseline mean arterial pressure [mean (SEM)] was higher after 750 mg of lithium [93.1 (1.7) versus 89.5 (1.9 mmHg, P = 0.014], and the subsequent rise in blood pressure during angiotensin II infusion was lower [8.2 (1.8) versus 12.2 (2.4) mmHg, P less than 0.02]. 3. Lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At the lower doses, RBF may decrease without changes in GFR or even with slight increases in GFR [1084] . Ang II infusions to humans elicit greater reductions in RBF in high sodium subjects than in the low sodium subjects; however, GFR is not significantly altered in either group [1085,1086] . Ang II infusions to humans elicit greater reductions in RBF in high sodium subjects than in the low sodium subjects; however, GFR is not significantly altered in either group [1085,1086] .…”
Section: Actions Of Ang II On Renal Microvasculature and Renal Hemodymentioning
confidence: 81%
See 1 more Smart Citation
“…At the lower doses, RBF may decrease without changes in GFR or even with slight increases in GFR [1084] . Ang II infusions to humans elicit greater reductions in RBF in high sodium subjects than in the low sodium subjects; however, GFR is not significantly altered in either group [1085,1086] . Ang II infusions to humans elicit greater reductions in RBF in high sodium subjects than in the low sodium subjects; however, GFR is not significantly altered in either group [1085,1086] .…”
Section: Actions Of Ang II On Renal Microvasculature and Renal Hemodymentioning
confidence: 81%
“…Similar responses result from low chronic doses infused directly into the renal artery for up to 5 days [759] . In other studies, Ang II infusion at 1, 4 and 8 pmol/kg/min into subjects maintained on high salt intake (340 mM) and taking enalapril to reduce endogenous Ang II levels [1085,1087,1088] , produced greater decreases in RBF than in GFR, but both decreased. In other studies, Ang II infusion at 1, 4 and 8 pmol/kg/min into subjects maintained on high salt intake (340 mM) and taking enalapril to reduce endogenous Ang II levels [1085,1087,1088] , produced greater decreases in RBF than in GFR, but both decreased.…”
Section: Actions Of Ang II On Renal Microvasculature and Renal Hemodymentioning
confidence: 84%
“…The effect of lithium pretreatment on U Na V has been debated for several years (12,33,42). To approach reliable plasma concentrations of Li for precise and accurate measurements, a test dose of 450 mg LiCO 3 was used in protocol 2 (46).…”
Section: Lithium and Renal Sodium Excretionmentioning
confidence: 99%
“…Previous studies in humans have also shed little light on the issue. Eadington et al [ 5 ] found that CLi following ingestion of 750 mg lithium carbonate was the same as that following a 250 mg dose. However, at the time clearances were performed, no natriuresis was apparent with either dose.…”
Section: Discussionmentioning
confidence: 92%